2023
DOI: 10.3390/s23136178
|View full text |Cite
|
Sign up to set email alerts
|

New Electronic Tongue Sensor Array System for Accurate Liquor Beverage Classification

Abstract: The use of sensors in different applications to improve the monitoring of a process and its variables is required as it enables information to be obtained directly from the process by ensuring its quality. This is now possible because of the advances in the fabrication of sensors and the development of equipment with a high processing capability. These elements enable the development of portable smart systems that can be used directly in the monitoring of the process and the testing of variables, which, in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…For several decades, there has been significant research on electronic tongue (E-tongue) systems that aim to mimic the human tongue. The importance of the E-tongue system lies in its ability to differentiate tastes from intricate samples at levels significantly below human perception. This is particularly vital in analyzing the tastes of beverages such as wines, beers, and coffees. Conventional sensory evaluations, conducted by sommeliers and experts, are constrained by susceptibility to environmental conditions, subjective influences, and mental and physical states . These factors may lead to the nonobjectiveness and uncertainty in evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…For several decades, there has been significant research on electronic tongue (E-tongue) systems that aim to mimic the human tongue. The importance of the E-tongue system lies in its ability to differentiate tastes from intricate samples at levels significantly below human perception. This is particularly vital in analyzing the tastes of beverages such as wines, beers, and coffees. Conventional sensory evaluations, conducted by sommeliers and experts, are constrained by susceptibility to environmental conditions, subjective influences, and mental and physical states . These factors may lead to the nonobjectiveness and uncertainty in evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…The e-tongue generally uses pattern recognition algorithms to identify the taste or avor of a sample using signals generated by non-speci c, cross-selectivity electrochemical sensors 7,8 . Since individual sensors do not have su cient sensitivity to discriminate different liquids, multiple electrochemical and/or biosensors combined with multivariate statistical data analysis are necessary 9,10 . For example, Rudnitskaya et al demonstrated a prediction of the Port wine age with high accuracy using 28 potentiometric chemical sensors combined with partial least squares (PLS) regression 11 .…”
Section: Introductionmentioning
confidence: 99%